Addressing the challenge of limited sample volumes in in vitro studies with capillary-scale microfluidic LC––MS/MS. (April 2011) - Rainville, Paul D; Smith, Norman W; Wilson, Ian D; Nicholson, Jeremy K; Plumb, Robert S
Miniaturization of chromatographic separation systems provides a means of greatly increasing sensitivity in LC––MS. In this article, we demonstrate the use of an integrated microfluidic chromatographic device for the LC––MS/MS investigation of the in vitro microsomal metabolism of the model drug propranolol using a sample volume of 1 µµl of a 1-µµM incubation. With such samples the system was capable of obtaining high-quality MS and MS/MS data from the injection of test drug substance containing sufficient information to correctly derive the structure of the drug metabolites. The analytical column was tolerant to the injection of a large percentage of organic solvent in the sample and still delivered a high-quality separation. The data suggest that these types of micro-LC––MS/MS devices are robust enough for routine applications and well suited to the analysis of small samples. Other potential applications include the generation of pharmacokinetic profiles from the reduced sample volumes obtained from serially bled small rodent studies, or the facilitation of analysis of limited-volume samples from neurological studies.